Allergen-Specific Immunotherapy With Liposome Containing CpG-ODN in Murine Model of Asthma Relies on MyD88 Signaling in Dendritic Cells - Alberca-Custodio, Ricardo Wesley; Faustino, Lucas D.; Gomes, Eliane; Nunes, Fernanda Peixoto Barbosa; de Siqueira, Mirian Krystel; Labrada, Alexis; Almeida, Rafael Ribeiro; Câmara, Niels Olsen Saraiva; da Fonseca, Denise Morais; Russo, Momtchilo (Frontiers in Immunology, 2020)
Changing the immune responses to allergens is the cornerstone of allergen immunotherapy. Allergen-specific immunotherapy that consists of repeated administration of increasing doses of allergen extract is potentially curative. The major inconveniences of allergen-specific immunotherapy include failure to modify immune responses, long-term treatment leading to noncompliance and the potential for developing life-threating anaphylaxis. Here we investigated the effect of a novel liposomal formulation carrying low dose of allergen combined with CpG-ODN, a synthetic TLR9 agonist, on established allergic lung inflammation. We found that challenge with allergen (OVA) encapsulated in cationic liposome reduced significantly active cutaneous anaphylaxis reaction when compared with non-encapsulated OVA. Notably, short-term treatment (three doses) with a liposomal formulation containing co-encapsulated allergen plus CpG-ODN, but not allergen or CpG-ODN alone, reversed an established allergic lung inflammation and provided long-term protection. This liposomal formulation was also effective against allergens derived from Blomia tropicalis mite extract. The attenuation of allergic inflammation was not associated with increased numbers of Foxp3-positive or IL-10-producing regulatory T cells or with increased levels of IFN-gamma in the lungs. Instead, the anti-allergic effect of the liposomal formulation was dependent of the innate immune signal transduction generated in CD11c-positive putative dendritic cells expressing MyD88 molecule. Therefore, we highlight the pivotal role of dendritic cells in mediating the attenuation of established allergic lung inflammation following immunotherapy with a liposomal formulation containing allergen plus CpG-ODN.